Ethnic Enclaves and the Dynamics of Social Identity on the College Campus The Good, the Bad and the Ugly . [article] . - Sidanius, Jim
The effects of membership in ethnic organizations and fraternities and sororities on intergroup attitudes were examined using a 5-wave panel study at a major, multiethnic university. The results showed that these effects were similar for both minority and White students. Membership in ethnic student organizations for minorities and Greek organizations for Whites was anteceded by the degree of one's ethnic identity, and the effects of membership in these groups were similar, although not identical, for both White and minority students. These effects included an increased sense of ethnic victimization and a decrease sense of common identity and social inclusiveness. Consistent with social identity theory, at least a portion of these effects were mediated by social identity among both White and minority students. -- (from the author)